Prenatal modulation of NADPH-oxidase reverses the deranged GABA switch and rescues behavioral deficits in valproate ASD rat model - Yasseen, Basma A.; Abdelkhalek, Hadeer; Gohar, Sara; Hatem, Yasmin; El-Sayed, Hajar; Elkhodiry, Aya A.; Galal, Aya; Samir, Aya; Al-Shehaby, Nouran; Elbenhawi, Malak W.; Hamdy, Rehab; Prince, Christine S.; et al. (Frontiers in Pharmacology, 2025)
IndroductionImpaired depolarizing-to-hyperpolarizing (D/H) switch of gamma-aminobutyric acid (GABA) is reported during brain development in rodent valproate-model of autism spectrum disorder (VPA-ASD). We hypothesize that this impairment triggers NADPH oxidases (NOXs)-induced reactive oxygen species (ROS) overproduction.MethodsHere, we followed the impact of prenatal exposure to VPA on the synaptic protein expression of potassium chloride cotransporter 2 (KCC2), sodium potassium chloride cotransporter 1 (NKCC1) and, in brains of male and female Wistar rats during infantile (P15), juvenile (P30) and adult (P60) stages. We also assessed alterations in synaptic NOX isoforms 2 and 4 (NOX2 and NOX4) activities and expressions in developing rat brains.ResultsOur findings revealed a significant reduction in KCC2 expression and a concomitant increase in NOX activity and NOX4 expression in synaptosomes of VPA-exposed rats, particularly at P15 and P30. Prenatal exposure to shikonin, (10 mg/kg/day, intraperitoneal (i.p.) into pregnant dam, daily from G12.5 until birth), ameliorated these effects by reducing synaptic protein expression of NOX4, generally quenched synaptic NOX activity and enhanced synaptic protein expression of KCC2. Indeed, shikonin reversed VPA-induced sociability deficits in ASD rats.DiscussionThese results suggest that targeting the NOX-ROS pathway may be a potential therapeutic strategy for ASD.